“Evolusi-Devolusi” Pemerintahan Demokratis dalam Nalar Filosofis Abdolkarim Soroush - Imron Mustofa (Universitas Darussalam Gontor, 2021)
This article tries to offer Abdolkarim Soroush answer to problem of inaccuracy of religious attitudes in addressing religion and democracy as a government system. In Soroush’s view, peoples sees ideology as no longer valid, when they keep on a single interpretation as solid idea. They prefer on compound, nonsecterian and charitable ideas. This study uses a philosophical-critical analysis method. The article confirms: Soroush offers a new kalām (theology) approach as intermediary way between Islam and social problems. As an intellectual-mondial, he want to present Islam that can be universally understood, follows world community common sense, is not just traditional textual approach. This option is quite sensitive and full of risk, like his criticism toward Iranian post-revolutionary government.